DIFFERENCES IN GAS VENTING FROM ULTRAMAFIC-HOSTED WARM SPRINGS: THE EXAMPLE OF OMAN AND VOLTRI OPHIOLITES - Boulart, Cédric; Chavagnac, Valérie; Monnin, Christophe; Delacour, Adélie; Ceuleneer, Georges; Hoareau, Guilhem (Ofioliti, 2012)
Serpentinisation of mantle rocks, leading to natural venting of hydrogen and methane, has been reported to occur at the global scale, wherever fluids percolate in ultramafic formations. Here we compare gas composition from two on-land, low-temperature, and hyper-alkaline springs hosted on ultramafic rocks in the ophiolite massifs of the Sultanate of Oman and the Ligurian Alps (Voltri Group, Genoa region, Northern Italy). These two settings exhibit similar chemical and mineralogical features but show diverse styles of gas venting. Commonly to all hyper-alkaline springs, gases are characterised by relatively high N2, very low O2 and CO2 concentrations, and a strong enrichment in H2 and CH4. The comparison between Oman and Liguria highlights a high variability of the H2/CH4 ratios whereby the gas phase of the Oman Ophiolite is enriched in H2 whereas being CH4 enriched in the Voltri Ophiolite. These results combined with literature data define three groups that may reflect different stages of serpentinisation producing fluids from hydrogen-dominated to methane-dominated. The origin of these distinct groups might lie in the difference of the mineralogical composition of the rocks within which the fluids circulate, on the degree of alteration of the rocks and finally on the geological/metamorphic history of the ophiolite.